Mre11-Rad50-Nbs complex is required to cap telomeres during Drosophila embryogenesis - Gao, Guanjun (National Academy of Sciences, 2009)
Using Drosophila as a model system, we identified here a stringent requirement for Mre11-Rad50-Nbs (MRN) function in telomere protection during early embryonic development. Animals homozygous for hypomorphic mutations in either mre11 or nbs develop normally with minimal telomere dysfunction. However, they produce inviable embryos that succumb to failure of mitosis caused by covalent fusion of telomeric DNA. Interestingly, the molecular defect is not the absence of MRN interaction or of Mre11 nuclease activities, but the depletion of the maternal pool of Nbs protein in these embryos. Because of Nbs depletion, Mre11 and Rad50 (MR) are excluded from chromatin. This maternal effect lethality in Drosophila is similar to that seen in mice carrying hypomorphic mrn mutations found in human patients, suggesting a common defect in telomere maintenance because of the loss of MRN integrity.